2021
DOI: 10.1002/app.51930
|View full text |Cite
|
Sign up to set email alerts
|

Silk fibroin electrospun nanofiber blends with antibiotics and polyvinyl alcohol for burn wound healing

Abstract: Silk fibroin, is a structural and protein‐based biomacromolecule produced from Bombyx mori silkworm. Silk fibroin has been widely being used for biomedical and biomaterial applications, tissue engineering, and drug delivery since a decade. The present study mainly focused to investigate the wound healing efficiency of the developed silk fibroin‐based extracellular electrospun nanofibrous matrix. Electrospun nanofibers were developed by blending the silk fibroin solution with antibiotics (Ciprofloxacin, Amoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…114 Table 1 summarizes the natural and synthetic polymers used in the preparation of electrospun nanober burn dressings. These polymers mainly include natural ones such as chitosan, [115][116][117][118][119][120] gelatin, [121][122][123] silk broin, 118,124,125 sodium alginate, 126,127 and synthetic polymers such as poly(3-caprolactone), [128][129][130][131][132] poly(vinyl alcohol), 119,125,133 poly(ethylene oxide), 120,127,131 poly(vinyl pyrrolidone), 132 polyurethane 126 and polylactic acid. 134 4.1 Natural polymers 4.1.1 Chitosan.…”
Section: Polymer Used For Making Electrospun Nanofiber Burn Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…114 Table 1 summarizes the natural and synthetic polymers used in the preparation of electrospun nanober burn dressings. These polymers mainly include natural ones such as chitosan, [115][116][117][118][119][120] gelatin, [121][122][123] silk broin, 118,124,125 sodium alginate, 126,127 and synthetic polymers such as poly(3-caprolactone), [128][129][130][131][132] poly(vinyl alcohol), 119,125,133 poly(ethylene oxide), 120,127,131 poly(vinyl pyrrolidone), 132 polyurethane 126 and polylactic acid. 134 4.1 Natural polymers 4.1.1 Chitosan.…”
Section: Polymer Used For Making Electrospun Nanofiber Burn Dressingsmentioning
confidence: 99%
“… 124 Yerra et al prepared electrospun nanofibers by blending silk fibroin, polyvinyl alcohol, and antibiotics. 125 The wound therapeutic effect of nanofiber dressing was tested by a rat burn model. The results showed that the dressing had excellent antibacterial ability, and it also promoted the cell viability and cell adhesion of fibroblasts.…”
Section: Polymer Used For Making Electrospun Nanofiber Burn Dressingsmentioning
confidence: 99%
“…Burns are a major global public health problem, and burn trauma can be caused by heat (flame or scald), freezing, electricity, chemicals, radiation, or friction. Skin repair after burns requires a complex process following trauma, including coagulation, inflammation, cell proliferation, and tissue remodeling [ 145 , 146 ]. Burns can cause damage to the protective skin barrier and lead to pathogen colonization of the burn wound site.…”
Section: Applicationmentioning
confidence: 99%
“… 11 , 12 One possible solution is the development of advanced burn wound healing materials, which could provide effective wound treatment while lowering the risk of complications. 3 , 13–15 …”
Section: Introductionmentioning
confidence: 99%